2020
DOI: 10.1128/msystems.00829-19
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Changes in Prokaryotic Communities in Artificial Pit Mud during Chinese Baijiu Production

Abstract: The Chinese alcoholic beverage strong-flavor baijiu (SFB) gets its characteristic flavor during fermentation in cellars lined with pit mud. Microbes in the pit mud produce key precursors of flavor esters. The maturation time of natural pit mud of over 20 years has promoted attempts to produce artificial pit mud (APM) with a shorter maturation time. However, knowledge about the molecular basis of APM microbial dynamics and associated functional variation during SFB brewing is limited, and the role of this varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 57 publications
1
19
1
Order By: Relevance
“…The diversity increased slightly after day 10, and many alcohol-tolerant microorganisms began to grow. The changes in environment and nutrition during brewing explain the changes in community species diversity [42]. The diversity index reflects the changes in the microbial community, as confirmed in the present study.…”
Section: Diversity Indexsupporting
confidence: 85%
“…The diversity increased slightly after day 10, and many alcohol-tolerant microorganisms began to grow. The changes in environment and nutrition during brewing explain the changes in community species diversity [42]. The diversity index reflects the changes in the microbial community, as confirmed in the present study.…”
Section: Diversity Indexsupporting
confidence: 85%
“…According to the national standard of strong-flavor baijiu (number GB/T 10781.1-2006) ( 5 ), the concentrations of total esters and ethyl hexanoate are set as key parameters to classify the quality grade. Both recent research and long-term production practice have highlighted the crucial roles of microbes inhabiting pit mud in the accumulation of typical flavor compounds (mainly hexanoic acid and butyric acid) of strong-flavor baijiu ( 6 8 ). Thus, elucidating the features of the pit mud microbial community structure and function will provide key information to understand the complex flavor formation mechanisms of strong-flavor baijiu.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the diversity and abundance of Clostridia were significantly higher in normal and high-quality pit mud than in the degraded samples, while Lactobacillus decreased with the improvement of quality ( 18 ). Accordingly, a major goal of pit mud production is to increase the levels of clostridial microbes to meet the target of hexanoic acid accumulation enhancement, which will further help improve product flavor ( 8 , 19 ). The main objective of this work was to explore the forces modulating the pit mud microbiome on the basis of the microbial community structure and metabolic characteristics analysis of different-aged samples.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial diversity in different PM has been widely revealed in recent years. Liu et al (2020) found that Clostridium and Bacillus were dominant bacterial genera in PM with high relative abundance during Chinese Baijiu production. However, there are significant differences in microbial community structure in different PM samples.…”
Section: Discussionmentioning
confidence: 92%